2023
DOI: 10.21203/rs.3.rs-2946547/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kaempferol suppresses inflammation in mice suffering from both hyperuricemia and gouty arthritis through inhibiting NLRP3 inflammasome and NF-κB pathway

Abstract: The co-occurrence of hyperuricemia and gouty arthritis is common in patients, yet a suitable animal model for this condition is lacking. In present study, a mice model combined hyperuricemia and gouty arthritis was established. Kaempferol, a flavonoid compound with anti-inflammatory and urate-lowering properties, was administered to mice in different dosages (25, 50, and 100 mg/kg). The levels of uric acid, creatinine, blood urea nitrogen and xanthine oxidase activity were measured, then kidney and joint ankle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Moreover, the urate excretion pathway in hyperuricemic mice was further analyzed. The dysregulation of urate transport-associated proteins (e.g., GLUT9, URAT1, OAT1, and OAT3) leads to renal insufficiency with renal uric acid reabsorption increased and excretion decreased, which was supposed to be the reason for the development of hyperuricemia in mice [60]. Our study indicated that the Hsp-Cu(II) complex downregulated URAT1 and GLUT9 protein expression and upregulated OAT1 protein expression.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, the urate excretion pathway in hyperuricemic mice was further analyzed. The dysregulation of urate transport-associated proteins (e.g., GLUT9, URAT1, OAT1, and OAT3) leads to renal insufficiency with renal uric acid reabsorption increased and excretion decreased, which was supposed to be the reason for the development of hyperuricemia in mice [60]. Our study indicated that the Hsp-Cu(II) complex downregulated URAT1 and GLUT9 protein expression and upregulated OAT1 protein expression.…”
Section: Discussionmentioning
confidence: 66%
“…Kaempferol, recognized for its anti-inflammatory and urate-lowering properties, was administered in various dosages (25, 50, and 100 mg/kg) to assess its impact on uric acid levels, renal function, and joint pathology. Through detailed examinations of kidney and joint tissues, the study delved into kaempferol's efficacy in mitigating hyperuricemia-induced damage [101]. Histological analyses confirmed that kaempferol effectively ameliorated glomerular and renal tubular lesions as well as inflammatory infiltration in the ankle joints induced by hyperuricemia combined with gouty arthritis.…”
Section: Kaempferolmentioning
confidence: 99%
“…Histological analyses confirmed that kaempferol effectively ameliorated glomerular and renal tubular lesions as well as inflammatory infiltration in the ankle joints induced by hyperuricemia combined with gouty arthritis. The study further explored the mechanisms underlying kaempferol's effects, focusing on its modulation of the NOD-like receptor protein 3 (NLRP3) inflammasome and the NF-κB pathway [101] (Figures 2 and 3).…”
Section: Kaempferolmentioning
confidence: 99%